Determinants of vitamin D status among Black and White low-income pregnant and non-pregnant reproductive-aged women from Southeast Louisiana - Burke, Natalie L. (BMC Pregnancy Childbirth, 2019)
BACKGROUND: Vitamin D deficiency is a growing public health problem, with pregnant women being particularly vulnerable due to its influences on maternal and neonatal outcomes. However, there are limited data published about mediators of vitamin D status in Louisiana women. We aimed to assess the vitamin D status and its determinants among low-income pregnant and non-pregnant reproductive-aged women from southeast Louisiana. METHODS: This study was conducted using data from the Gulf Resilience on Women’s Health (GROWH) research consortium cohort of pregnant and non-pregnant women which contained sociodemographic and dietary variables as well as blood and salivary element concentrations. Serum 25-hydroxy vitamin D was measured using an enzyme-linked immunosorbent assay in 86 pregnant and 98 non-pregnant women with an even distribution of race in both groups. RESULTS: The prevalence of deficient vitamin D levels in the total cohort (184 women) was 67% and the mean 25(OH) vitamin D(3) was 24.1 ng/mL (SD 10.7). Self-identifying as White, being pregnant, autumn season, young age and high exposure to tobacco smoke measured by cotinine were significantly associated with higher serum levels of vitamin D. Visiting Women and Infant clinics (WIC) was an important determinant in improving 25(OH) vitamin D(3) levels for Black women but not for White women and concentrations varied more among Black women across seasons compared to White women. CONCLUSIONS: Serum vitamin D levels are inadequate among a high proportion of Black and White low-income pregnant and reproductive-aged women living in Southeast Louisiana who were enrolled in the GROWH study. Black women who are over 35 years old and non-WIC participants constitute the subpopulation most at risk for vitamin D deficiency, especially during the winter. As an overall higher level of deficiency exists in Black women, if even small behavioral and dietary modifications are produced by WIC, this can lead to a comparatively greater improvement in vitamin D status in women from Southeast Louisiana who self-identify as Black.